Silver silence : a Psy-changeling trinity novel - Singh, Nalini, 1977- (Singh, Nalini, 1977- Psy-changeling novel., 2017)
"New York Times bestselling author Nalini Singh returns to her extraordinary Psy-Changeling world with a story of wild passion and darkest betrayal ... Control. Precision. Family. These are the principles that drive Silver Mercant. At a time when the fledgling Trinity Accord seeks to unite a divided world, with Silver playing a crucial role as director of a worldwide emergency response network, wildness and chaos are the last things she needs in her life. But that's exactly what Valentin Nikolaev, alpha of the StoneWater bears, brings with him. Valentin has never met a more fascinating woman. Though Silver is ruled by Silence--her mind clear of all emotion--Valentin senses a whisper of fire around her. That's what keeps him climbing apartment buildings to be near her. But when a shadow assassin almost succeeds in poisoning Silver, the stakes become deadly serious"--